1999
DOI: 10.1046/j.1469-8137.1999.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Apical meristems of tomato roots and their modifications induced by arbuscular mycorrhizal and soilborne pathogenic fungi

Abstract: Functional morphological patterns in root apices of tomato (Lycopersicon esculentum) dependent on growth, ageing and infection by the arbuscular mycorrhizal (AM) fungus Glomus mosseae and\or by the soilborne pathogenic fungus Phytophthora nicotianae var parasitica (P. parasitica) were studied. Uninfected root apices were characterized by closed, tri-layered meristems with nonreticulate nuclei ; however, some apices of each treatment lost their meristematic nature, stopped growing and differentiated, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 42 publications
(59 reference statements)
2
14
1
3
Order By: Relevance
“…However, since root-rot pathogens usually infect immediately behind the root tip, the higher number of root tips in inoculated plants could have lead to an increase of their susceptibility to rootrot, as indicated by Norman et al (1996) who showed an increased rate of infections by root-rot pathogen in more branched root systems. But, AM fungi also had a positive effect on the size of root apices which then appear to be less susceptible to pathogen infections (Fusconi et al, 1999). This observation could account for the disease suppression achieved by G. mosseae BEG12 recorded in the present study despite its positive effect on the number of root tips.…”
Section: Discussionmentioning
confidence: 84%
“…However, since root-rot pathogens usually infect immediately behind the root tip, the higher number of root tips in inoculated plants could have lead to an increase of their susceptibility to rootrot, as indicated by Norman et al (1996) who showed an increased rate of infections by root-rot pathogen in more branched root systems. But, AM fungi also had a positive effect on the size of root apices which then appear to be less susceptible to pathogen infections (Fusconi et al, 1999). This observation could account for the disease suppression achieved by G. mosseae BEG12 recorded in the present study despite its positive effect on the number of root tips.…”
Section: Discussionmentioning
confidence: 84%
“…Mycorrhizal fungi may be capable of altering root physiology in non-nutritional ways. For example, Fusconi et al (1999) observed that AM fungi increased the size of the root apex in tomato, which was associated in this case with more sustained root growth. This may have also occurred in our study, where sustained growth rate was an important feature of mycorrhizal apple roots (Fig.…”
Section: Lack Of Colonization By Both Mycorrhizal and Nonmycorrhizal mentioning
confidence: 93%
“…It has been proposed (Baumgartner 2004) that alleviation of pathogen impact on plant yield and growth could be used as a measure of the efficacy of control methods of Armillaria root disease. The improved growth in M plants inoculated with the pathogen could be due to a better compensation for the damage caused by the pathogen (Aguin-Casal et al 2006;Pozo et al 2002) or to changes in mycorrhizal root architecture that may provide fewer sites for infection (Fusconi et al 1999;Norman et al 1996). At the end of the second growing year, although the pathogen caused a decrease in aerial and root biomass, plants associated to AMF grew significantly better indicating that AMF inoculation alleviated disease symptoms.…”
Section: Discussionmentioning
confidence: 99%